Rocketdyne powering humans into space - Kraemer, Robert S.; Wheelock, Vince (American Institute of Aeronautics and Astronautics, 2006)
From the first US orbiting satellite, to Neil Armstrong, and Buzz Aldrin's walk on the Moon, almost every achievement in US Space history was helped by a Rocketdyne engine. This is the chronicle of a team's success that propelled the US space program from trailing the Soviet Union in the 1950s and early 1960s into a position of space leadership.